2000
DOI: 10.1111/j.1365-2621.2000.tb10261.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Transmission Rates and Sorption Behavior of Chitosan Films

Abstract: This study measured the water vapor transmission rates (WVTR) and moisture sorption of chitosan films over a range of water vapor pressures at 25°C. Films of a constant thickness were made using chitosan with 3 levels of deacetylation. Films were tested at test relative humidity (RH) difference between RH values of 84%, 75%, 69%, 53%, 43%, 33%, 23%, 11%, and 0 at 25°C using ASTM F1249-90 or ASTM E 96-80. The equilibrium moisture content in the films ranged from 3.7% to 31.8% (dry basis) corresponding to 11% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 11 publications
10
49
0
3
Order By: Relevance
“…These functions of chitosan may be related to decrease fruit respiration, resulting in less weight loss (Gonza´lez-Aguilar, Buta, & Wang, 2003;Sivakumar et al 2005;Xianghong, Li, Liu, & Tian, 2008). Dong et al (2004) also found that the properties of film formed by chitosan, including moisture barrier and selective permeability of gas, are related to its concentration (Wiles, Vergano, Barron, Bunn, & Testin, 2000;Park, Marsh, & Rhim, 2002). Thus, the results indicated that chitosan at conc.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These functions of chitosan may be related to decrease fruit respiration, resulting in less weight loss (Gonza´lez-Aguilar, Buta, & Wang, 2003;Sivakumar et al 2005;Xianghong, Li, Liu, & Tian, 2008). Dong et al (2004) also found that the properties of film formed by chitosan, including moisture barrier and selective permeability of gas, are related to its concentration (Wiles, Vergano, Barron, Bunn, & Testin, 2000;Park, Marsh, & Rhim, 2002). Thus, the results indicated that chitosan at conc.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, Dutta et al (2009) also cited that chitosan acts as an inhibitor to various enzymes, leading to delay fruit senescence. However, the property of film formed by chitosan, including selective permeability of gas, is related to its molecular characteristic and concentration (Park et al, 2002 andWiles et al, 2000). There are several results showing that application of chitosan coating effectively extended shelf-life of peeled Litchi fruit (Huaqiang et al, 2004), papaya (Ali, Eryani, & Raqeeb, 2008), avocado (Salvador, Miranda, Aragon, & Lara, 1999), fresh-cut Chinese water chestnut , tomato (El Ghaouth, et al, 1992a), longan fruit (Jiang & Li, 2001), fresh-cut strawberries (Campaniello, Bevilacqua, Sinigaglia, & Corbo, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already demonstrated the antibacterial and antifungal action of this compound for both bioactive preservative and bioactive packaging applications (Chung et al, 2004;Coma et al, 2002;Fernandez-Saiz, Ocio, & Lagaron, 2006;Moller, Grelier, Pardon, & Coma, 2004;Shahidi & Abuzaytoun, 2005). Systematic research has also been reported on the effect of plasticizers concentrations, storage time (Butler, Vergano, Testin, Bunn, & Wiles, 2006), acid types and concentrations (Caner, Vergano, & Wiles, 1998), molecular weight (Park, Marsh, & Rhim, 2002) and degree of deacetylation of chitosan (Wiles, Vergano, Barron, Bunn, & Testin, 2000) on the physical properties of chitosan films. Concerning the mode of action of chitosan films, it has already been well demonstrated that its biocide effect is generally related to the release from the biopolymer of protonated glucosamine fractions into the culture medium (Fernandez-Saiz, Lagaron, Hernandez-Muñoz, & Ocio, 2008;Fernandez-Saiz et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Differences in the sources of chitin used to produce chitosan, chitosan properties, solvents used, methods of film preparation, and types and amounts of plasticizers used affected the quality of the chitosan films [247,248]. The filmforming ability of chitosan extracted from crawfish has also been reported [249].…”
Section: Film-forming Ability Of Chitosanmentioning
confidence: 99%